A Study on Evaluating the Impact of Social Media Analytics on Consumer Behaviour and Brand Loyalty - Ragul, S; Kesavaraj, Geeta (Shanlax International Journal of Management, 2025)
This study explores the impact of Social Media Analytics (SMA) on consumer behaviour and brand loyalty. The research aims to assess how businesses leverage SMA to track engagement, sentiment, and demographic trends, ultimately influencing consumer attitudes and purchasing decisions. A mixed-method approach, incorporating quantitative surveys and qualitative secondary data analysis, was employed to examine these relationships. Key findings indicate a strong positive correlation between effective SMA use and increased consumer engagement, trust, and brand advocacy. Study finds that SMA’s influence remains consistent across different demographic groups. These insights underscore the strategic advantage of data-driven marketing, highlighting that brands utilizing SMA effectively can foster long-term consumer relationships and enhance retention. The study emphasizes the necessity for businesses to integrate SMA into digital marketing strategies to maintain a competitive edge in an evolving online marketplace.